Investigating the impact of the education level of construction owners on business performance - Makalichi, Silas (Department of Construction Economics and Management, 2023)
The study investigates the impact of the level of education of owners on the performance of the business in the construction industry. Construction companies are key to economic development in South Africa, playing an economic role in the nation's GDP and solving economic problems like unemployment and equitable distribution of wealth, among other things. The construction industry is one of the industries with very high employment potential in South Africa; therefore, the success of the small businesses in the industry is key to the nation's success. Previous research in the field of business identified several parameters that affect business performance and among these is the human capital of the business (education level of managers and owners). However, limited studies have examined the level of education of business owners and how this impacts the performance of the construction business. So, this study aims to find the common level of education of business owners, the typical performance of the businesses and whether the level of education impacts the performance. The following objectives were used to achieve this; to find out the level of education of business owners in the construction industry; to establish the typical level of performance of construction businesses; to determine the perception of business owners on the impact of education on construction company performance and; to find out whether the level of education of business owners' impacts construction company performance. A quantitative research design approach was adopted using a questionnaire survey, administered using email, to obtain information from a sample population of 40 contractors that were being managed by Navi Professional consulting on Sanitation projects in the Mpumalanga Province of South Africa. The data collected were analysed using descriptive statistics that include cross-tabulations and histograms of the education parameters. A Chi-square statistical analysis was conducted to test the hypothesis but established that the level of education of construction owners does not significantly impact business performance. Based on the findings, the study concludes that the level of education of the business owner is not a significant factor that impacts the performance of construction businesses. It is therefore recommended that in order to avert failure, construction business owners should learn from their experience and continuos on-the-job training. Further research that examines the impact of the level of education of construction owners on business performance using a larger sample size is also recommended.